Optimization: In-Depth Examination and Proposition - Phan, Huy Phuong; Ngu, Bing Hiong; Yeung, Alexander Seeshing (Frontiers in Psychology, 2019)
One notable concept that is of interest is a person’s state of optimal functioning. Achieving optimal functioning (e.g., subjective well-being at school), aside from personal autonomy, requires some form of ‘optimization’. Optimization, we argue, is more than just an ‘enhancement, a ‘predictive effect’, and/or a ‘causal flow’ between an independent variable (IV) and a dependent variable (DV). We note from existing literature that optimization has often been referred to without a clear, definitive explanation of what this term actually entails. At the same time, we acknowledge that unlike other areas of development (e.g., engagement), no theoretical article is available to explain the concept of optimization. This article considers a number of theoretical tenets for advancement: (i) the tenet of three major criteria that could assist in the explanation, assessment, and measurement of optimization, (ii) the tenet of the development of a methodological conceptualization that could measure and assess optimization, and (iii) the tenet of the ‘quantification’ of optimization and, in particular, a proposed index of optimization and a corresponding scientific notation of ‘γ’, which we coin as an ‘optimizing effect’. Overall, we contend that this examination is insightful and holistic, seeking clarity into an important topical theme in psychology.